EVALUASI PENERAPAN PSAK 30 TENTANG SEWA PEMBIAYAAN KONSUMEN PADA ASTRA CREDIT COMPANIES (ACC) DI MANADO - Gani, Fajriah; Ilat, Ventje; Tirayoh, Victorina Z. (GOING CONCERN : JURNAL RISET AKUNTANSI, 2017)
The emergence of leasing agency is  an attractive for enterpreneurs Because today they tend to use cash rupiah fund for operational, activites of the company. Through leasing they could obtain funds to finance the purchase of capital goods with a repayment period of between three to five years or more. The object of this research is  Astra Credit Companise which is the largest auto finance company in Indonesia. The purpose of this research is to analyze the accounting treatment of leasing and reporting on Astra Credit Companaise in Manado. The method used is descriptive method, to identify the data that is used in connection with the assets that will be in the leasing of vehicles, identify the system of recording and reporting of leasing transactions, evaluating the advantages / disadvantages  in accounting for leasing transactions and reporting of leasing transactions, as well as draw conclusions. The results of the research can be in the know that leasing has several types and classifications as well as the criteria for determining the accounting system. The accounting treatment and reporting of leasing transactions on Astra Credit Companaise using leasse capital system where the lease can be transferred ownership at the end of the lease term. Based Recording aspect, reporting and disclosure, the accounting treatment of leasing at Astra Credit Companaise in accordance with SFAS applicabl.Keywords : Application of consumer finance lease, PSAK No.30